Efektivitas Jamu Untuk Perawatan Pasca Stroke Di Rumah Riset Jamu (RRJ) Hortus Medicus Tawangmangu - Ratnawati, Galuh (Jurnal Farmasi Udayana, 2020)
The use of jamu for the treatment of disease has become a method of choice besides conventional treatment using modern medicine, including by stroke survivors. Rumah Riset Jamu (RRJ) Hortus Medicus is a B2P2TOOT’s research house that conducts health service-based research. RRJ Hortus Medicus developed jamu concoctions for post-stroke care containing celery (Apium graveolens L.), gotu kola (Centella asiatica L.), and sembung (Blumea balsamifera L.). This study aims to see the effectiveness of the jamu concoctions. A total of 106 post-stroke patients were recorded having repeated treatment at the RRJ Hortus medicus which was entered from 2013 to 2018. The medical records of these 106 patients were traced and analyzed. The effectiveness parameter assessed was the Neurological Impairment Scale (NIS) score. Jamu concoctions can improve the NIS score average in 58% of patients, which means that jamu concoctions have the potential to be further developed as jamu concoctions for post-stroke care in accordance with BPOM requirements. Jamu was also well tolerated by the research subjects in the absence of any serious side effects after taking jamu concoctions.